Ascaroside signaling in C. elegans. - Ludewig, Andreas H (s.n.], 2013)
Over the past 10 years, the relevance of small-molecule signaling for many aspects of C. elegans development and behavior has become apparent. One prominent group of small-molecule signals are the ascarosides, which control dauer entry and exit as well as a variety of sex-specific and social behaviors, including male attraction, hermaphrodite repulsion, olfactory plasticity, and aggregation. This wide range of biological functions is facilitated by a great diversity of ascaroside chemical structures. These are based on the sugar ascarylose, which is linked to fatty acid-like side chains of varying lengths and often decorated further with building blocks derived from amino acids, folate, and other primary metabolites. Different ascarosides or combinations of ascarosides mediate different phenotypes, and even small differences in chemical structures are often associated with strongly altered activity profiles. Additional complexity arises from concentration-dependent effects and synergism between different ascarosides. The ascarosides are sensed by several types of chemosensory head neurons, including the ASK, ASI, and ADL neurons as well as the male-specific CEM neurons. Ascaroside perception is mediated by diverse families of G-protein coupled membrane receptors that act upstream of conserved signal transduction pathways, including insulin/IGF-1 signaling and transforming growth factor beta (TGF-β) signaling. Biosynthesis of the ascarosides appears to integrate input from several primary metabolic pathways, including peroxisomal β-oxidation of long-chain fatty acids and amino acid catabolism. Life stage, sex, as well as food availability and other environmental factors affect ascaroside biosynthesis, suggesting that ascaroside signaling communicates detailed information about life history and metabolic state.